Effectiveness of Planned Teaching Program on Knowledge Related to Diaper Dermatitis among the Mothers - B. Kale, Aparna (International Journal of Nursing Research, 2023)
Aim: The aim of this study was to assess the effectiveness of planned teaching program on knowledge related to diaper dermatitis among the mothers. Introduction: Diaper dermatitis is also known as diaper rash. Almost every mother and child has had some experience with diaper rash at some time. To many 1st-time mothers, a case of diaper rash may shake their confidence in their ability to be an adequate mother and to care for their infant. Objective: The present study was carried out to assess the pre-existing knowledge related to diaper dermatitis among the mothers of children age (0–1 year) and effectiveness of planned teaching program on knowledge related to diaper dermatitis. Methodology: The research design used was one group pre-test – post-test design to collect the sample constitutes; 70 mothers of children (0–1 year) in pediatric unit of selected hospitals from Sangli-Miraj Area. Results: Results of present study shown that the knowledge of the mothers of pre-test mean score is 8.08, standard deviation is 1.79, and in post-test mean score is 12.17, standard deviation is 1.65, t = 35.64 and P = 0.000, that is, it is highly significant as P < 0.005; therefore, there is increase in the knowledge score after planned teaching program. Conclusion: The present study shows that the planned teaching program was effective. The study findings could be utilized in various matter as well and recommended in developing better manner.